2020
DOI: 10.1177/1362168820914025
|View full text |Cite
|
Sign up to set email alerts
|

A self-paced reading (SPR) study of the effects of processing instruction on the L2 processing of active and passive sentences

Abstract: Recent research on the effects of processing instruction (PI) have incorporated online research methods in order to demonstrate that PI has effects on cognitive processing behaviors as well as on accuracy (e.g. Lee & Doherty, 2019a). The present study uses self-paced reading and a moving windows technique to examine the effects of PI on second language (L2) learners’ processing of Spanish active and passive sentences to explore the effects of PI on instructed second language acquisition. One group received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…(2016) demonstrated the effectiveness of video games on learning outcomes. Previous research has demonstrated the effectiveness of sentence–picture matching tasks on learning outcomes (Lee et al., 2020; Malovrh et al., 2020). These studies also show that learning takes place in groups as well as in individual (isolated) settings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(2016) demonstrated the effectiveness of video games on learning outcomes. Previous research has demonstrated the effectiveness of sentence–picture matching tasks on learning outcomes (Lee et al., 2020; Malovrh et al., 2020). These studies also show that learning takes place in groups as well as in individual (isolated) settings.…”
Section: Discussionmentioning
confidence: 99%
“…We presented linguistic input via self-paced (moving-windows) reading, which allows us to examine word-by-word processing and determine which words in a sentence require the most cognitive effort (Lee et al, 2020;Malovrh, et al 2020). We used the laboratory setting to create the learning environment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Relatively few studies have used cognitive behavioral measures such as self-paced reading (SPR) or eye-tracking to investigate how PI and related instructional interventions change learners' processing strategies, though these methodologies are becoming more common in PI research. As Lee et al (2020) and Henry (2022) discuss, these studies address an increasingly large number of research questions, but many have centered on the effects of PI compared to other instructional trainings (Benati, 2020a(Benati, , 2020bChiuchiù & Benati, 2020;Henry, 2022;Issa & Morgan-Short, 2019;McManus & Marsden, 2017Wong & Ito, 2018) and on aspects of a PI training, such as the delivery of explicit information (EI) or feedback (Dracos & Henry, 2018;Indrarathne & Kormos, 2017;Issa, 2019;Wong & Ito, 2018). While these studies have utilized a variety of methodological approaches, the research has broadly found that PI increases attention and sensitivity to the target forms (Henry, 2022;Issa & Morgan-Short, 2019), reduces the use of nontarget processing strategies (Dracos & Henry, 2018;Wong & Ito, 2018), and/or increases depth or ease of processing (Chiuchiù & Benati, 2020;Lee et al, 2020).…”
Section: The Effects Of Training On Processingmentioning
confidence: 99%